Flat fibre and femtosecond laser technology as a novel photonic integration platform for optofluidic based biosensing devices and lab-on-chip applications: Current results and future perspectives - Kalli, Kyriacos; Riziotis, Christos; Posporis, Andreas; Markos, Christos; Koutsides, Charalambos; Ambran, Sumiaty; Webb, Andrew Simon; Holmes, Christopher H.; Gates, James C; Sahu, Jayanta Kumar S; Smith, Peter George R (My University, 2015)
Flat optical fibre technology is a glass-based substrate technology that has emerged recently, it offers a flexible and potentially very long, distributed sensing medium, whilst also having increased lateral and vertical dimensions; this allows for the development of optical integrated circuits with the enhanced functionality promised by optical chips. In this work we report on recent developments to highlight the incorporation of integrated structures on the surface and in the bulk volume of flat fibres using femtosecond laser inscription. This fusion of two innovative technologies, and in particular the flexibility afforded by femtosecond laser inscription and micromachining, has led to the realisation of microfluidic channels, ring resonators, resonator disc, Mach-Zehnder and complex microfluidic designs in the surface of the optical chip, whereas Bragg grating waveguides have been recorded in the bulk volume of the optical chips. The flat-fibre platform offers a unique degree of freedom by allowing surface and sub-surface devices to be integrated onto a single optical chip with the potential for straightforward incorporation into integrated photonic circuits or opto-fluidic devices.
Keywords: Bragg grating; Femtosecond laser; Flat fibre; Integrated optics; Micro-optical components; Planar; Sensors